20 year trends in renal disease mortality in Ghana: A review of autopsies. Issue 4 (27th March 2019) - Adjei, David N; Adu, Dwomoa; Quayson, Solomon E; Kardaun, Jan WPF; Erskine, Isaac J; Lartey, Isaac S; Agyemang, Charles
ABSTRACT: Aim: Data on the changing levels in renal morbidity and mortality are scant globally. We sought to assess trends in renal disease mortality and attributable causes over a 20 year period in Ghana. Methods: A retrospective analysis of 20 year autopsy records of the Pathology Departments of leading teaching hospitals in Ghana, (Korle‐Bu Teaching Hospital (KBTH) in Accra and Komfo Anokye Teaching Hospital (KATH) in Kumasi) from January 1994 to December 2013. Data comprising autopsies from in‐patients, community cases and coroners' cases were used. We defined primary cause of death as death directly due to renal disease and secondary cause of death as death in which renal disease was a comorbid or contributing factor. Results: Over the period, there were a total of 94 309 deaths, of which 5608 were attributed to renal disease (5.9/100). Mortality rate remained fairly the same from 1994 to 2009 (5.0%), but doubled from 2010 to 2013 (10.8%). Similar trends were observed among males and females during the same period. However, males had slightly higher mortality rates (6.6%; 95% CI: 46.1%–6.8%) compared to females (5.6%; 95% CI: 5.4%–5.8%; P = 0.271). The major leading attributable causes of renal disease death include end stage renal disease 45.0% and acute pyelonephritis accounting for 20.9% of the cases. Hypertensive heart disease accounted for 30.0% of all secondary cause of death while congestive heart disease and septicaemia accounted for 13.0% and 12.0%, respectively. Conclusions: We observed marked increase in the renal disease mortality rate during the last few years predominantly driven by chronic and infectious related renal diseases as a main cause, and hypertensive heart disease and congestive heart failure as the main secondary causes. Measures geared towards prevention, treatment and managing such conditions may impact on the reduction of renal disease mortality rate among Ghanaian populations. Summary at a Glance: A retrospective analysis of 20 year autopsy records of the Pathology Departments of leading teaching hospitals in Ghana, to identify the contribution of renal disease as a cause of death. 5.9% of all deaths were attributed to renal causes. Mortality rates attributed to renal disease had increased from 5.0% in the 1990s to 10.8% over the past 3 years.